POLYELECTROLYTE MEMBRANE AND ITS MANUFACTURING METHOD - KUNO SHINJI; HIRANO TETSUHARU (2007)
PROBLEM TO BE SOLVED: To provide a method for manufacturing a polyelectrolyte membrane as a self-sustaining membrane which is easily peelable from a support such as a metal belt made of stainless, etc. when the membrane is manufactured as composed of a polyelectrolyte having strong acid groups or super-strong acid groups. SOLUTION: The manufacturing method by casting of the polyelectolyte membrane having a strong acid group or a super-strong acid group comprises a step of casting on the support a polyelectrolyte solution containing 0.0005 to 2 pts.wt. of a specific phosphate, and/or a specific salt of an amine and a phosphate to 100 pts.wt. of a specific polyelectrolyte; evaporating a solvent by heating so that the cast solution becomes the self-sustaining membrane; and peeling the self-sustaining membrane from the support. COPYRIGHT: (C)2007,JPO&INPIT